Posibilities of use of remote sensing technologies in the castle island measuring process in jelgava - Celms, A.; Reke, I.; Pukite, V.; Kolodiy, P.; Luksa, J. (Видавництво Львівської політехніки, 2020)
New technologies come into area of surveying more rapidly. By them work can be done safer, faster and in more interesting way and one of the newest technologies is laser scanning, result of which is point cloud, from which diverse three-dimensional models can be created. By combining photogrammetry and laser scanning methods, it is possible to obtain many-sided digital material of high quality, which is used for purposes of designing, project supervision, thus people's work is facilitated and made easier, in particular in places, which have difficult access or access can be life-threatening. The digital material, in this case relief model, allows performing above-mentioned activities remotely. For the achievement of the aim, following tasks were set: to study the available information on historical development of photogrammetry and laser scanning and principles of functioning of them; to research, analyse and describe strategy and program of sustainable development of Jelgava City; to analyse the situation of the planned Northern Flyover; to obtain spatial data for location of the planned Northern Flyover; to perform spatial data processing.
Keywords: laser scanning; relief model; photo visualization; 528.88(474.334.2)